Los hallazgos de mamíferos fósiles durante el período colonial en el actual territorio de la Argentina - Pasquali, Ricardo (2008)
A review of the discoveries of fossil vertebrates in the colonial period and their historical context, is carried out in this paper. The discoveries of great size fossil vertebrates during this period, were awarded to an old race of giant humans. An alternative hypothesis, attributed the presence from these enormous bony remains to the capacity that possess certain terrains of to increase the bones excessively. The Jesuit Thomas Falkner discovers in 1760 the first remains of a glyptodont. An interesting progress in the interpretation of this type of remains was the correct identification carried out for academic of the Real Academia de la Historia of Spain of a supposed burial of rational with a giant stature discovered in Arrecifes in 1766. The most significant discovery during the colonial period is that of the skeleton of Megatherium americanum (Luján, 1787); it was described by Georges Cuvier, being based on a notable unpublished study of the Spanish naturalist Juan Bautista Brú de Ramón.